The European Society of Head and Neck Radiology Mentoring Programme: development and feedback during the first phase of the initiative - Steve Connor (SpringerOpen, 2021)
Abstract There is increasing awareness of the benefits of formal mentorship programmes in radiology. In the context of the COVID 19 pandemic which impacted on education, professional engagement and networking within the wider radiological community, the European Society of Head and Neck Radiology (ESHNR) decided to develop a formal mentoring programme. The ESHNR mentoring initiative is novel in its scope, whereby European and international members of a subspecialty radiology society are matched into mentor–mentee pairings to disseminate good practice, knowledge and ideas. The purpose of this report is to describe the motivations, planning, challenges and early experience of the ESHNR mentoring programme together with initial feedback from the scheme. The development of the programme and iterative modifications during the first phase of the scheme are described. The programme has enrolled 33 mentors and 27 mentees with international representation and 24 mentor–mentee pairs have participated in 2.6 (mean) meetings. The experience and benefits reported by the participating ESHNR members (mentees and mentors) were evaluated by a questionnaire at six months following the start of the programme. There were 80% of mentors and 88% of mentees who strongly agreed that the mentoring programme was rewarding rather than an obligation, and all participants reported that they would recommend the scheme to colleagues. A formal mentoring programme has been established for an international subspecialty radiology society. The early experience is encouraging and suggests that it is both useful and sustainable. Our experiences may be of benefit to other subspecialty societies considering a mentoring programme.